2022
DOI: 10.1007/s00405-022-07558-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of cochlear reserve in adults with cochlear implants following post-lingual hearing loss

Abstract: Introduction Pre-operative assessments before cochlear implantation (CI) includes the examination of both tone hearing, and the level of the cochlear reserve indicated by speech understanding. The goal of this study was to explore the predictive influence of tone hearing and cochlear reserve in CI. Methods We did a retrospective cohort study, which included adult patients who had undergone CI between January 2012 and December 2019 in a tertiary care center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 26 publications
5
23
0
2
Order By: Relevance
“…However, because of the limitations intrinsic to any retrospective studies, our predictive models did not include variables such as daily CI wear time, aided WRSs, and duration of severe-to-profound SNHL, which are thought to add predictive power to postimplantation outcomes (36,37). More recent studies have shown that aided preoperative measures of speech recognition may provide a predictive value re postoperative outcomes (17,18,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, because of the limitations intrinsic to any retrospective studies, our predictive models did not include variables such as daily CI wear time, aided WRSs, and duration of severe-to-profound SNHL, which are thought to add predictive power to postimplantation outcomes (36,37). More recent studies have shown that aided preoperative measures of speech recognition may provide a predictive value re postoperative outcomes (17,18,38).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis including more than 1,000 patients from 13 studies, age at implantation was found to be the only non-negligible predictor statistically associated with postimplantation performance on word or sentence recognition in quiet (9). More recently, it was found that adding a WR test in aided conditions to the preoperative test battery could improve the predictability of postoperative performances of CI recipients (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…In einer früheren Studie [ 13 ] wurde gezeigt, dass das präoperativ gemessene mEV als unterer Schätzer für das mit CI erreichbare Sprachverstehen verwendet werden kann. Jüngere Arbeiten bestätigen dieses Ergebnis [ 14 , 27 ]. Unlängst wurde für Patienten mit Hörverlusten < 80 dB HL ein Vorhersagemodell für das mit CI zu erwartende Einsilberverstehen entwickelt, das auf den präoperativ bekannten Größen mEV, Einsilberverstehen mit Hörgerät bei 65 dB SPL , EV 65 (HG), und dem Lebensalter zum Zeitpunkt der Versorgung besteht [ 14 ], siehe Gl.…”
Section: Quantifizierung Des Sprachverstehensunclassified
“…In 8 Fällen (6,5 %) ist das EV 65 (CI) signifikant [ 10 ] geringer als das mEV. Insgesamt zeigt sich hier eine weitgehende Übereinstimmung mit einer andernorts durchgeführten Studie [ 27 ], welche auch auf die große Bedeutung des mEV im Rahmen der CI-Versorgung hinweist.…”
Section: Diskussionunclassified
“…Cochlear implantation is an established treatment option for patients with hearing loss for which hearing aids (HAs) or other less invasive options have failed to restore speech perception to a sufficient degree [ 1 ]. The vast majority of cochlear implant (CI) recipients show improved word recognition scores (WRSs) if the pre-operative-aided scores at a conversational level of 65 dB (WRS 65 (HA)) and post-operative scores with a CI (WRS 65 (CI)) are compared [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. A number of pre-, intra- and post-operatively assessed outcome-predicting factors have been identified [ 2 , 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%